2016
DOI: 10.1021/acs.biochem.5b01141
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Methods To Investigate lncRNA and the Influence of lncRNA:Protein Complexes on Chromatin

Abstract: Long noncoding RNAs (lncRNAs), defined as non-translated transcripts greater than 200 nucleotides in length, are often differentially expressed throughout developmental stages, tissue types, and disease states. The identification, visualization, and suppression/overexpression of these sequences have revealed impacts on a wide range of biological processes, including epigenetic regulation. Biochemical investigations on select systems have revealed striking insight into the biological roles of lncRNAs and lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 167 publications
0
38
0
Order By: Relevance
“…Additional high-throughput screens could likewise discover novel chemotypes, though the expense may exceed the resources available in academia, where focused approaches are more attainable. Continued progress in the development and refinement of computational tools will also aid in expanding the boundaries of focused screening and structure-based design;( 56 , 57 ) although the latter will also depend upon advancements for accurately determining atomic resolution structures ( 8 , 9 , 37 , 38 ). In addition, in vitro or cellular activity-based assays that probe well-studied RNA functions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional high-throughput screens could likewise discover novel chemotypes, though the expense may exceed the resources available in academia, where focused approaches are more attainable. Continued progress in the development and refinement of computational tools will also aid in expanding the boundaries of focused screening and structure-based design;( 56 , 57 ) although the latter will also depend upon advancements for accurately determining atomic resolution structures ( 8 , 9 , 37 , 38 ). In addition, in vitro or cellular activity-based assays that probe well-studied RNA functions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The higher hit rates found in some FcS approaches provide compelling evidence that FcS is efficient for RNA targets, as it is known to be for protein targets ( 35 , 36 ). Moving forward, characterization of additional RNA tertiary structures ( 8 , 9 , 37 , 38 ) and the identification of novel RNA-binding chemotypes ( 8 , 39 , 40 ) will expedite the FcS approach for discovering biologically active RNA-targeted ligands. While hit rates varied widely within each type of primary screen and primary library, these comparisons support the potential of many distinct paths toward RNA ligand discovery.…”
Section: Discovery and Design Of Rna-targeted Small Molecule Chemicalmentioning
confidence: 99%
“…A variety of experimental techniques such as SHAPE chemical probing in combination with bioinformatics prediction methods have been developed to characterize the secondary structures of several lncRNAs in vitro (such as HOTAIR [28] and SRA [29]) or in vivo (such as PAN [4]) [30]; unfortunately, three-dimensional structural characterization of lncRNAs like sfRNAs is still challenging to traditional techniques like X-ray crystallography (XRC), nuclear magnetic resonance (NMR), and cryo-electron microscopy (cryo-EM) [31][32][33]. Recent progress in small angle X-ray scattering (SAXS) has made it a powerful tool in bridging the gap between the secondary and tertiary structures and characterizing the accessible 3D conformational space of large RNAs in solution [34,35], and SAXS might be the only reasonable method for directly acquiring structural data for large RNAs [36].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Unger et al demonstrated that stroma-induced insulin-like growth factor 2 (IGF-2) can promote colon cancer progression in a paracrine and an autocrine manner (8). Long non-coding RNAs (lncRNAs) are mostly defined as a class of non-coding RNAs exceeding 200 nucleotides in length (9). Increasing evidence has demonstrated that lncRNAs play key roles in regulating Comprehensive analysis of differential expression profiles of mRNAs and lncRNAs and identification of a 14-lncRNA prognostic signature for patients with colon adenocarcinoma many crucial biological processes such as genetic imprinting, cell differentiation, apoptosis and cell proliferation, and immune responses.…”
Section: Introductionmentioning
confidence: 99%